Navigational Display - Srivinay, Srivinay; T, Spurthy K; Deepika, C (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2019)
An appropriate integrated display system to display the current information of the ship is essential to help the ship officers in the decision making process. Navigational display is proposed to improve the efficiency for a safe navigation. By using Qt application software, current information of the own ship and target such as range, bearing, longitude, and latitude, are displayed at the top left corner of the radar screen display.